Investigation of morphological degradation of P3HT:PCBM bulk heterojunction films exposed to long-term host solvent vapor. Issue 10 (15th February 2016) - Wang, Weijia; Guo, Shuai; Herzig, Eva M.; Sarkar, Kuhu; Schindler, Markus; Magerl, David; Philipp, Martine; Perlich, Jan; Müller-Buschbaum, Peter
Abstract : A solvent atmosphere results in the degradation of P3HT:PCBM solar cells due to the formation of large PCBM crystallites. Abstract : Solution-based processing procedures are widely used during the fabrication of polymer solar cells both on the lab scale and in industrial applications. The understanding of device stability in its host solvent vapor atmosphere is of great significance to the fabrication, encapsulation and storage. Solar cells with poly(3-hexylthiophene):[6, 6]-phenyl-C61 butyric acid methyl ester (P3HT:PCBM) bulk heterojunction (BHJ) active layers are prepared with different solvents of chlorobenzene, toluene, xylene and dichlorobenzene. The stability is investigated via exposure to their respective host solvent vapor for a long period. All solar cells strongly degrade after exposure to solvent vapor for long-term and only the dichlorobenzene-related device still shows reasonable function. The morphology of P3HT:PCBM BHJ films is probed using optical microscopy, atomic force microscopy, grazing incidence small and wide angle X-ray scattering and absorption measurements. The solvent induced PCBM crystallization is identified as the main reason for device failure.